2010
DOI: 10.1007/s00360-010-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Overwinter body temperature patterns in captive jerboas (Jaculus orientalis): influence of sex and group

Abstract: The jerboa (Jaculus orientalis) has been described in the past as a hibernator, but no reliable data exist on the daily and seasonal rhythmicity of body temperature (T (b)). In this study, T (b) patterns were determined in different groups of jerboas (isolated males and females, castrated males and grouped animals) maintained in captivity during autumn and winter, and submitted to natural variations of light and ambient temperature (T (a)). T (b) and T (a) variations were recorded with surgically implanted iBu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Indeed, Siberian hamsters adapted to a short photoperiod display a decrease in body weight associated with an increase in Somatostatin gene expression (Herwig et al, ; Dumbell et al, ). In the present study, we observed a significant increase in Somatostatin gene expression in spring as compared to autumn, which is in line with the reported decrease in the jerboa's body weight in spring and summer (El Ouezzani et al, ). Therefore, Siberian hamster and jerboa appear to display opposite but coordinated seasonal variations in both Somatostatin gene expression and body weight.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, Siberian hamsters adapted to a short photoperiod display a decrease in body weight associated with an increase in Somatostatin gene expression (Herwig et al, ; Dumbell et al, ). In the present study, we observed a significant increase in Somatostatin gene expression in spring as compared to autumn, which is in line with the reported decrease in the jerboa's body weight in spring and summer (El Ouezzani et al, ). Therefore, Siberian hamster and jerboa appear to display opposite but coordinated seasonal variations in both Somatostatin gene expression and body weight.…”
Section: Discussionsupporting
confidence: 92%
“…It displays seasonal variations in the nocturnal production of melatonin (Lakhdar-Ghazal et al, 1992) and melatonin inhibits testicular activity in male jerboas (El Qandil et al, 2004). Additionally, previous studies reported that jerboas display seasonal variations in body weight and food intake (El Ouezzani et al, 2011;Talbi et al, unpublished data). The seasonal changes in reproductive activity are accompanied by variations in the content of hypothalamic peptides involved in the central control of reproductive activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The differential effect of Kp on females’ food intake may be related to their different sexual and energy status between both seasons. Indeed at spring, when coming out of hibernation, female jerboas are sexually active with reduced body weight35 and express higher ARC Kp immunoreactivity18 as compared to autumn. It might be interesting to compare Kiss1r distribution and Kp neuronal connection to POMC and RFRP neurons between spring and autumn to help understand the seasonal differences in the metabolic action of Kp.…”
Section: Discussionmentioning
confidence: 99%
“…The jerboa is a particularly interesting animal model living in a semi-desert milieu characterized by large annual variations in environmental temperature, water and food supply. In autumn/winter, when the natural conditions are unfavorable, jerboas shut down their reproductive activity3233, increase their food intake and body weight and hibernate3435, while in spring/summer when favorable conditions return, the animals display opposite regulations with a reactivation of reproduction and reduction in body weight and food intake32333536.…”
mentioning
confidence: 99%